SISTEM INFORMASI PERSEDIAAN OBATBERBASIS WEB DI RUMAH SAKIT BINA KASIH - AHMAD ZAINUDIN; Andik Prakasa Hadi; AGUS PRIYADI (Jurnal Ilmiah Sistem Informasi, 2024)
Effective drug inventory management is essential for hospital pharmacy management to prevent stock shortages and waste due to expiration. Bina Kasih Hospital faces obstacles such as manual recording and reporting difficulties. This study designs a web-based drug inventory information system with waterfall methodology, using PHP, MySQL, and Bootstrap interface. This system allows real-time data access, stock tracking, automatic notification, and data integration. Testing using black-box and user acceptance testing showed increased operational efficiency, with a reduction in recording errors of up to 80% and an acceleration of reporting of up to 50%. This system supports auditing, reporting, and data integration. This solution is expected to optimize Bina Kasih Hospital's pharmacy management, with the potential for further development for integration with electronic medical record modules and procurement systems.